Obtenção de quitosana reticulada por processamento termomecânico para aplicações biomédicas - Silva, Maria Conceição Ramos da Soledade Bezerra (2022)
The low processability of chitosan and the obtaining of materials with low structural stability constitute substantial limitations to the commercial use of chitosan, especially in biomedical applications. Furthermore, the need to neutralize chitosan as a biomaterial increases the inherent fragility of these materials. Thus, this thesis was developed to obtain chitosan-based materials with structural integrity in the swollen state and advantageous mechanical and physicochemical properties using a thermomechanical processing route. For this, the chemical crosslinking strategy with citric acid was adopted. The citric acid (CA), in three different concentrations, was evaluated as a destructuring agente and crosslinking agent and compared to material traditionally processed with acetic acid. The chemical structure, the destructuring capacity of chitosan powder, morphology, and physicochemical and mechanical properties indicated the occurrence of chemical crosslinking, decreased crystallinity, and increased physicochemical and mechanical properties with increasing CA content. Morphological analysis revealed never-before-seen structures related to the crosslinked material's mechanical properties. In addition, a neutralization route in a buffered medium was proposed, minimizing possible hydrolysis reactions in strongly alkaline media. The glycerol was reincorporated into the materials by immersion, and it was found that the absorbed content is proportional to the immersion time. The flexibility of the materials was recovered without damage to the mechanical strength, and the exudate retention capacity was defined for application as dressings in moderately exuding wounds. The drug release profile showed a controlled release capacity for eight days during the in vitro assay for tetracycline hydrochloride. The results suggest that a chitosan-based biomaterial can be obtained by thermomechanical processing with structural stability in the swollen state and that the neutralization and plasticization strategies effectively provide properties similar to the original materials.